Pengaruh Iklim Kerja dan Motivasi Berprestasi terhadap Kinerja Guru Madrasah Tsanawiyah Negeri Kota Pekanbaru - Rahmadanni Pohan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research aimed to find out whether there was a significant effect of work climate and achievement motivation on teachers’ performances of State Islamic Junior High School in Pekanbaru. Used correlation method with quantitative approach. The total number of respondents was 30 teachers. Technique of collecting the data used observation, questionnaire and documentation. Technique of analyzing the data used qualification test which consists of normality test, linearity and homogeneity test, and hypothesis test which was done by using simple correlation analysis, multiple correlation and determination analysis (R2) which entirely used SPSS version 22.0. The result showed that work climate gave effects on teachers’ performances of Islamic State Junior High School in Pekanbaru which was at a very strong category was 0.989, achievement motivation gave effects on teachers’ performances of Islamic State Junior High School in Pekanbaru which was at a very strong category was 0.993. Furthermore, work climate and achievement motivation simultaneously gave effects on teachers’ performances of Islamic Junior High School which was at a very strong category was 0.994. If work climate and achievement motivation increase, teachers’ performances of Islamic State Junior High School in Pekanbaru will be higher. Conversely, if the work climate and achievement motivation decrease, teachers’ performances of Islamic State Junior High School in Pekanbaru will be lower. From these results, it is expected that teachers can maintain and enhance their performance in completing the tasks optimally.